Deep insight into the Sb(III) and Sb(V) removal mechanism by Fe–Cu-chitosan material. (15th June 2022) - Wang, Tianning; Jiao, Yonghong; He, Mengchang; Ouyang, Wei; Lin, Chunye; Liu, Xitao; Xie, Haijiao
Abstract: Currently, alleviating antimony (Sb) contamination in aqueous solutions is crucial for restoring and recovering ecological and environmental health. Due to its toxicity, bioaccumulation and mobile characteristics, developing an efficient technique for antimony decontamination is imperative. Herein, we prepared a Fe–Cu-chitosan (FCC) composite by a one-step coprecipitation method, in which nanoscale Fe/Cu acts as the active sites and the whole structure is exhibited as porous microscale particles. A Fe/Cu proportion of 2/1 (FCC-2/1) was determined to be the optimum proportion for antimony adsorption, specifically 34.5 mg g −1 for Sb(III) and 26.8 mg g −1 for Sb(V) (initial concentration: 5.0 mg L −1 ). Spectral characterization, batch experiments and density functional theory (DFT) simulations were applied to determine the adsorption mechanism, in which surface hydroxyls (-OH) were responsible for antimony complexion and Fe–Cu coupling was a major contributor to adsorption enhancement. According to kinetic analysis, Cu provided an electrostatic attraction during the adsorption process, which facilitated the transportation of antimony molecules to the material interface. In the meantime, the FCC electronic structure was modified due to the optimization of the Fe–Cu interface coupling. Based on the Mullikan net charge, the intrinsic Fe–O–Cu bond might favor interfacial electronic redistribution. When the antimony molecule contacted the adsorption interface, the electrons transferred swiftly as Fe/Cu 3d and O 2p orbital hybridization occurred, thus inducing a stabilizing effect. This work may offer a new perspective for binary oxide construction and its adsorption mechanism analysis. Graphical abstract: Image 1 Highlights: An Fe–Cu-chitosan material was synthesized for antimony removal. The porous structure exposes more active sites for antimony complexion. The interfacial coupling of Fe–Cu optimizes the intrinsic electronic structure. The intrinsic Fe–O–Cu further serves as a path for interfacial electron transfer.